Eksploitasi Perempuan dalam Aplikasi Michat Ditinjau dari Perspektif Filsafat Feminis Mary Wollstonecraft - Yusi Saniah (Gunung Djati Conference Series, 2023)
This study aims to discuss the exploitation of women in the michat application from the perspective of the philosopher Mary Wollstonecraft. This study uses a qualitative approach by applying the library study method. The material object of this research is the exploitation of women, while the formal object is the perspective of the philosopher Mary Wollstonecraft. The scope of research is the social media space for the michat application. The results and discussion in this study indicate that according to research findings, certain users are involved in the practice of exploiting women in online messages by displaying their bodies via live streaming and choosing to book hotel rooms or other accommodations on the michat application. This study concludes that based on Mary Wollstonecraft's review of philosophical thought, women are exploited on the michat app not only because they are willing to do so, but also because social class dictates that women exist so that a wider audience knows about them. This study recommends related institutions to monitor the media space in preventing the exploitation of women in the michat application.